Effect of Balneotherapy on Skin Lesion at Hot Springs in Southern Ethiopia: A Single-Arm Prospective Cohort Study - Gebretsadik A (Dove Medical Press, 2023)
Achamyelesh Gebretsadik School of Public Health, College of Medicine and Health Sciences, Hawassa University, Hawassa, Southern Nation Nationalities People Region, EthiopiaCorrespondence: Achamyelesh Gebretsadik, School of Public Health, Hawassa University, P.O. Box 1466, Hawassa, Ethiopia, Tel +251 911303128, Email agtsadik@gmail.comBackground: Balneotherapy is the use of mineral water for the treatment of a wide range of diseases including skin lesions. Even though Ethiopia has a large number of places with natural hot springs, their therapeutic value has not been thoroughly studied. The aim of this study was to determine the effect of balneotherapy among patients with skin lesions at hot springs in southern Ethiopia.Methods: A single-arm prospective cohort study design was used to assess patient's progress from their skin lesion complaint after using the hot water for at least three consecutive days or more. An individual visiting the hot springs site and staying there for at least three days or more was included in the study. From four hot springs sites in Southern Ethiopia, 1320 study participants who were 18 years of age or older were enrolled. The data were gathered using a standardized questionnaire and a physical examination. A descriptive analysis was made.Results: Of the total, 142 (10.8%) of them had various skin lesions. Flexural lesions accounted 87 (61.3%), non-specific skin conditions 51 (35.9%), co-lesions at the scalp, external ear canal, trunk, and various locations, and psoriatic lesions comprised 4.8%. There were 72 (82.8%) typical eczematous lesions among the total number of flexural lesions. After using balneotherapy for 3- 7 days once daily, 69 (95.2%) cases of eczematous dermatitis and 30 (58.8%) cases of non-specific skin issues showed improvement from the lesion. Additionally, after 30 days of bathing once daily, the PASI score of more than 90% of the psoriatic cases dropped to a score of one.Conclusion: Patients with skin lesions benefit significantly from balneotherapy when it lasts for three or more days. In order to improve skin lesions, proper application for at least a week or longer is highly beneficial.Keywords: balneotherapy, hot springs, skin lesion, southern Ethiopia